KOMPETENSI APARATUR DESA, SISTEM PENGENDALIAN INTERNAL DAN PEMANFAATAN TEKNOLOGI INFORMASI TERHADAP AKUNTABILITAS PENGELOLAAN DANA DESA - Anggy Putri Aulia Fernanda; Wida Fadhlia (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2022)
This study aims to determine the effect of the village apparatus competence, internal control systems, and the use of information technology on the accountability of village fund management in the Village Government in Aceh Besar District. Data was collected by distributing 86 research questionnaires to respondents, namely the Village Treasurer or Finance Officer, the questionnaires which as many 86 questionnaires were completely answered. Determination of the sample using simple random sampling technique and analyzing the data using multiple linear regression model with SPSS version 28 program. The results of this study based on the responses received from 86 respondents indicate that (1) the competence of village officials affects the accountability of village fund management, (2) the internal control system affects the accountability of village fund management, (3) the use of information technology does not affect the accountability of village fund management, (4) the competence of the village apparatus, the internal control system and the use of information technology simultaneously affect the accountability of village fund management.